Influence of posterior tibial slope on knee flexion in posterior stabilized fixed bearing primary total knee arthroplasty - Kanugula, Sandeep Kumar; Rathod, Mallesh; S. M., Venugopal; Lebaku, Mohan Babu (International Journal of Research in Orthopaedics, 2020)
Background: The goal of total knee arthroplasty (TKA) is to relieve pain and maintain stable range of motion (ROM) for day to day activities. Among the various factors, posterior tibial slope slope (PTS) may play an important role in achieving good postoperative knee flexion. Our study aims to know the effectiveness of PTS on the ROM of the knee in a posterior cruciate ligament (PCL)-substituting TKA. Methods: A total of 125 unilateral PCL-substituting TKA’s were included in the study. Based on postoperative PTA which was measured on lateral radiograph, patients were divided into 3 groups, Group A (PTS of ≤2) comprise of 24 patients. Group B consists of 91 patients (PTS of 3 to 7). Group C includes 10 patients (PTS of 8 or more). Functional outcome was measured by using knee society score (KSS) and Western Ontario and McMaster Universities osteoarthritis index (WOMAC) which were evaluated preoperatively and at 18months post operatively. Results: Mean postop ROM was 92.91 ± 10.632; 107.24±10.905; 107.49±13.944 in group A, B, C respectively which was significantly related to mean postop PTS (0.74; 5.62; 9.87 in group A, B, C respectively) (P<0.05). Functional outcome was measured by KSS and WOMAC which showed no significant difference pre and postoperatively. Conclusions: The results of our study validate the hypothesis that a positive correlation exists between the postoperative flexion and PTS in the PCL-substituting TKA, an increase in PTS can lead to a greater degree of the knee flexion for every extra degree of PTS.